Quality of Life in Papillary Thyroid Microcarcinoma Patients Undergoing Radiofrequency Ablation or Surgery: A Comparative Study - Lan, Yu; Luo, Yukun; Zhang, Mingbo; Jin, Zhuang; Xiao, Jing; Yan, Lin; Zhu, Yaqiong (Frontiers in Endocrinology, 2020)
Objective: Papillary thyroid microcarcinoma (PTMC) has a good prognosis and a longterm survival, the health-related quality of life (HRQoL) is vital for PTMC survivors during their entire survivorship. Ultrasound (US)-guided radiofrequency ablation (RFA) has been introduced as an alternative to surgery for the patients with low-risk PTMC with high efficacy and safety. However, the assessment of QoL of patients with PTMC has not been specially reported. The aim of this study was to compare HRQoL between PTMC patients underwent RFA and surgery. Methods: From October 2019 to December 2019, 88 PTMC patients were enrolled in our study, including 54 in RFA group and 34 in surgery group, retrospectively. Three questionnaires including the 36-item short form health survey (SF-36), thyroid cancerspecific quality of life (THYCA-QOL), and Fear of Progression Questionnaire-Short Form (FoP-Q-SF) were obtained and analyzed in each patient. The scores were compared after adjusting for age, sex, medical expense and follow-up time. Results: According to the SF-36, the score of role limitation due to physical problems and emotional problems(RP, RE) as well as Physical Component Summary (PCS) showed a significant negative linear association between the RFA group and surgery group: RP(coefficient p<0.001,.064], p = 0.004), and PCS (coef: -8.312 [CI -13.694 to -2.930], p=0.003). The THYCA-QOL also showed statistically significant difference between the two groups with the domain for the problem of scar (coef: 10.246 [CI 1.330 to 19.162], p = 0.025 according to the multivariate analysis), suggesting a higher level of complaint in the surgery group than in the RFA group. There was no significant difference in fear of progression scores between the two groups. Conclusions: In patients with PTMC, US-guided RFA offers advantage over surgery in terms of HRQoL, which supports the role of RFA as an alternative strategy to surgery.